SYSTEMATIC LITERATURE REVIEW (SLR) : KEBIJAKAN PENDIDIKAN DALAM PEMBELAJARAN DI SEKOLAH DASAR - Kartini Ester; Ida Bagus Putu Arnyana; I Gede Margunayasa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to conduct a Systematic Literature Review (SLR) related to Policies and Learning Strategies in Primary Education. The SLR method by Kitchenham & Charters is used in three phases: Planning, Conducting, and Reporting. This review summarizes 15 Internasional articles that explore various dimensions of policy in primary education. The research shows that policy reforms, such as educational decentralization, teacher autonomy, and technology integration, have a significant impact on teaching practices and student engagement. Several studies highlight the importance of a collaborative culture in schools as a determining factor for the successful implementation of policies. In a broader context, these articles identify the challenges faced by schools in maintaining practices aligned with policies, especially in an era of increased educational accountability. Emphasis on professional development for teachers and ongoing training has been shown to enhance the quality of education and student learning outcomes. Additionally, policies that support inclusive learning models show positive impacts, improving educational access for students with special needs. The research also indicates that better implementation of evidence-based policies can strengthen the relationship between theory and practice and assist in guiding decision-making in education. Overall, these findings reinforce the importance of collaboration among stakeholders in the education sector and the need for evidence-based approaches in designing and implementing effective educational policies. Further research is needed to explore the long-term effects of implemented policies on teaching and learning practices in primary schools.